Sex Modulates Cardiovascular Effects of Icodextrin-Based Peritoneal Dialysis Solutions - Paniagua, Ramón; García-López, Elvia; Ávila-Díaz, Marcela; Ventura, María-de-Jesús; Orihuela, Oscar; Prado-Uribe, María-del-Carmen; Gallardo-Montoya, Juan-Manuel; Lindholm, Bengt (Frontiers in Physiology, 2022)
Background/Aims. Some previous observations have noted that after six months of peritoneal dialysis (PD) treatment with icodextrin solutions, blood pressure (BP) and NT-proBNP tend to return to baseline values. This may be due to accumulation of icodextrin products that exert a colloid osmotic effect, which drives water into the bloodstream, causing the rise in blood pressure. Since icodextrin is metabolized by α-Amylase and its gene copies are lower in females than in males, we hypothesized icodextrin metabolites reach higher concentrations in females and that cardiovascular effects of icodextrin are influenced by sex. Methods. Secondary analysis of a RCT comparing factors influencing fluid balance control in diabetic PD patients with high or high average peritoneal transport receiving icodextrin (n=30) or glucose (n=29) PD solutions. Serum icodextrin metabolites, osmolality, body composition and Inferior Vena Cava (IVC) diameter were measured at baseline, and at 6 and 12 months of follow-up. Results. After six months of treatment, icodextrin metabolites showed higher levels in females than in males, particularly G5-7 and >G7, serum osmolality was lower in females. In spite of reduction in total and extracellular body water, ultrafiltration (UF) was lower and IVC diameter and BP increased in females, suggesting increment of blood volume. Conclusion. Females undergoing PD present with higher levels of icodextrin metabolites in serum that may exert an increased colloid-osmotic pressure followed by less UF volumes and increment in blood volume and blood pressure. Whether this could be due to the lesser number of α-Amylase gene copies described in diabetic females deserves further investigation.